Endothelial cells promote migration and proliferation of enteric neural crest cells via β1 integrin signaling - Nagy, Nandor; Mwizerwa, Olive; Yaniv , Karina; Goldstein, Allan M. (Developmental biology, 2009)
Enteric neural crest-derived cells (ENCCs) migrate along the intestine to form a highly organized network of ganglia that comprises the enteric nervous system (ENS). The signals driving the migration and patterning of these cells are largely unknown. Examining the spatiotemporal development of the intestinal neurovasculature in avian embryos, we find endothelial cells (ECs) present in the gut prior to the arrival of migrating ENCCs. These ECs are patterned in concentric rings that are predictive of the positioning of later arriving crest-derived cells, leading us to hypothesize that blood vessels may serve as a substrate to guide ENCC migration. Immunohistochemistry at multiple stages during ENS development reveals that ENCCs are positioned adjacent to vessels as they colonize the gut. A similar close anatomic relationship between vessels and enteric neurons was observed in zebrafish larvae. When EC development is inhibited in cultured avian intestine, ENCC migration is arrested and distal aganglionosis results, suggesting that ENCCs require the presence of vessels to colonize the gut. Neural tube and avian midgut were explanted onto a variety of substrates, including components of the extracellular matrix and various cell types, such as fibroblasts, smooth muscle cells, and endothelial cells. We find that crest-derived cells from both the neural tube and the midgut migrate avidly onto cultured endothelial cells. This EC-induced migration is inhibited by the presence of CSAT antibody, which blocks binding to β1 integrins expressed on the surface of crest-derived cells. These results demonstrate that ECs provide a substrate for the migration of ENCCs via an interaction between β1 integrins on the ENCC surface and extracellular matrix proteins expressed by the intestinal vasculature. These interactions may play an important role in guiding migration and patterning in the developing ENS.